2019
DOI: 10.1016/j.cpr.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence: A qualitative systematic review and meta-synthesis of patients' experiences

Abstract: Fear of cancer recurrence (FCR) is a significant issue for most cancer survivors, which is now extensively confirmed by the scientific literature in the psycho-oncology field. We aimed to further explore the experience of having FCR from the point of view of patients by systematically reviewing qualitative studies. Following PRISMA guidelines, 64 qualitative studies were selected. All participants' quotes about FRC were identified, then analysed using a conceptual framework based on the emotion-focused therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 81 publications
7
68
1
1
Order By: Relevance
“…In the oncology setting, fear of cancer recurrence is widely acknowledged to interfere with health behaviours. For some, the fear of illness may drive unnecessary or excessive engagement with health services while for others, fear may serve to delay seeking care when needed [58, 59]. In our study, carers reported worries that their loved one with SMA at times underestimated their symptoms or tried to ignore indications of declining function.…”
Section: Discussionmentioning
confidence: 85%
“…In the oncology setting, fear of cancer recurrence is widely acknowledged to interfere with health behaviours. For some, the fear of illness may drive unnecessary or excessive engagement with health services while for others, fear may serve to delay seeking care when needed [58, 59]. In our study, carers reported worries that their loved one with SMA at times underestimated their symptoms or tried to ignore indications of declining function.…”
Section: Discussionmentioning
confidence: 85%
“…Cancer is one of the major noncommunicable chronic diseases that seriously affect human health (1)(2)(3). Although treatment methods and drug research and development continue to improve, many problems such as drug resistance and recurrence still hinder progress (4)(5)(6)(7)(8)(9). The treatment of malignant tumors encompasses multidisciplinary comprehensive diagnosis and treatment (10)(11)(12) and reasonable combination and arrangement of multiple treatment methods including surgery, radiotherapy, chemotherapy, targeted therapy, immunotherapy, endocrine therapy, interventional therapy (13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…While some work has been previously done exploring predictors of FCR, summarised in systematic reviews such as by Simard et al, these have been primarily demographic or disease related. Previous research regarding psychological, social, or environmental predictors, has mostly been qualitative, although complementary quantitative research in this area is increasing. Smith et al recently explored the role of metacognitions and cognitive style in relation to FCR, finding that psychological factors (ie, more intrusive thoughts and negative beliefs about worry) play an important role in FCR morbidity after controlling for demographic/medical factors.…”
Section: Discussionmentioning
confidence: 99%